PO4 Alternative Culture to Produce Phycocyanin and Protein as Potential additive food from Native Cyanobacterial Biomass - MACHADO-CEPEDA, Samanta; Rodriguez Jasso, Rosa; Ruiz , Hector Arturo (Revista Productos Naturales, 2025)
Rice husk can be used as a culture medium for cyanobacteria to obtain industrial compounds. One is phycocyanin, which is valued for its fluorescent properties and use as a food pigment with health benefits. This work validated its production using cyanobacteria and rice husk as an alternative medium. The rice husk compositions and carbohydrate content were analyzed using the Anthrone Method. Four concentrations of rice husk extract  were tested in 2L in flask photoreactors with an air supply of approximately 136 mL/min versus a control condition with BG-11 as synthetic media.
Keywords: Biorefinery; rice husk; circular bioeconomy; organic culture